Characterization of smoke for spacecraft fire safety. (October 2019) - Wang, Xiaoliang; Zhou, Hao; Arnott, W. Patrick; Meyer, Marit E.; Taylor, Samuel; Firouzkouhi, Hatef; Moosmüller, Hans; Chow, Judith C.; Watson, John G.
Abstract: Conventional spacecraft smoke detectors are not optimized for detecting space smoke, which differs from that on Earth due to the fuel materials, burning conditions, particle formation/transformation processes, and lack of gravity. More effective smoke detectors can be developed with knowledge of smoke chemical compositions, size distributions, optical properties, and emission factors specific to spacecraft-relevant materials, e.g., Poly(methyl methacrylate) (PMMA), cotton, and Nomex ® fabric. In normal gravity testing it is found that carbon is the main smoke component, with elemental carbon constituting ∼90% of particle mass for flaming PMMA combustion and organic matter constituting ≳80% of particle mass for other fuels and test conditions. Particles emitted from flaming PMMA are fractal-like soot agglomerates, different from the near spherical particles found for other fuels and burning conditions. Particle size distributions vary during the combustion process. When particle concentrations are near maximum, smoldering cotton generates bimodal number size distributions, while other fuels and test conditions exhibit unimodal lognormal number size distributions. Smoke particles from flaming PMMA combustion are black with single scattering albedos <0.3, while particles from other burned materials demonstrate low light absorption, with single scattering albedos >0.9 at 405–781 nm. Mass extinction coefficients are 7.8 m 2 /g for flaming PMMA and 2.7–4.2 m 2 /g for smoldering combustions at 632.8 nm. CO and PM2.5 emission factors are higher for smoldering than for flaming combustions, while CO2 emission factors are higher for flaming combustions. Highlights: Smoke particles are mainly composed of elemental and organic carbon. Particles are unimodal or bimodal lognormal distributions with mean diameters <200 nm. Particles from flaming PMMA are agglomerates with low single scattering albedo. Other particles are nearly spherical with high single scattering albedo. Smoldering and flaming emission factors are quantified for different fuels.